Human adenovirus type 7 subunit vaccine induces dendritic cell maturation through the TLR4/NF-κB pathway is highly immunogenic - Li, Yaru; Yang, Xia; Zhao, Renshuang; Xiu, Zhiru; Li, Shanzhi; Li, Yue; Song, Gaojie; Ge, Chenchen; Fang, Jinbo; Han, Jicheng; Zhu, Yilong; Li, Yiquan (Frontiers in Cellular and Infection Microbiology, 2023)
Human adenovirus type 7 (HAdv-7) infection is the main cause of upper respiratory tract infection, bronchitis and pneumonia in children. At present, there are no anti- adenovirus drugs or preventive vaccines in the market. Therefore, it is necessary to develop a safe and effective anti-adenovirus type 7 vaccine. In this study, we designed a recombinant subunit vaccine expressing adenovirus type 7 hexon protein (rBV-hexon) to induce high-level humoral and cellular immune responses. To evaluate the effectiveness of the vaccine, we first detected the expression of molecular markers on the surface of antigen presenting cells and the secretion of proinflammatory cytokines in vitro. We then measured the levels of neutralizing antibodies and T cell activation in vivo. The results showed that the rBV-hexon recombinant subunit vaccine could activate the innate immune response, including the TLR4/NF-κB pathway which upregulated the expression of MHCI, CD80, CD86 and cytokines. The vaccine also triggered a strong neutralizing antibody and cellular immune response and activated T lymphocytes. Therefore, the recombinant subunit vaccine rBV-hexon promoted humoral and cellular immune responses, thereby potentially enhancing protection against HAdv-7 infection.